Establishing foreign higher education institutions in Indonesia - Nadia Fairuza Azzahra; Natasya Zahra (Center for Indonesian Policy Studies (CIPS), 2023)
The government has granted authority for foreign higher education institutions (FHEIs) to establish a physical campus in Indonesia as first stipulated in the Minister of Research, Technology, and Higher Education Regulation (MRTHE) No. 53/2018. Given the poor quality of the local higher education institutions (HEI), which is attributed to several factors such as the low quality of teaching, research and human resources, limited funding, and poor governance, the arrival of FHEIs in Indonesia provides an opportunity for Indonesian students to acquire a world-class education at home, which would otherwise not be provided. The MRTHE regulation No. 53/2018 required all FHEIs to form a partnership with a local HEI in academia, research, and innovation. However, this regulation does not apply to FHEIs established in Indonesia's Special Economic Zone as stipulated in the MOEC Regulation No. 10/202. As these partnerships could potentially be difficult to initiate without a regulating provision, there is space for the Ministry of Education, Culture, Research, and Technology (MOECRT) to take on a leading role in facilitating these partnerships.
Keywords: 330